Modelling of transversal crack and delamination under traction with XFEM - Abdullah, Nur Azam; Curiel-Sosa, J.L.; Taylor, Zeike A.; Tafazzolimoghaddam, Behrooz; Vicente, J.L Martinez (2017)
This paper presents a new investigation on the computational modelling of crack and delamination on laminates composite. Extended Finite Element Model (XFEM) is used to model the transversal cracks (intralaminar) and delamination (interlaminar). The integration of fracture laws and constitutive equations are applied to assist the initiation of crack and delamination, and their subsequent evolution. Size effect study for the increment of composite volume on blocking ply is also included in this investigation. The results show very good agreement with the previous experimental and analytical data of each specimen and comparable with the previous literatures by Hallet et al. (transversal crack and delamination) and by Wisnom et al. (laminates size effect study).